High-strength halogen-free flame-retardant phenolic paper-based pressing plate and preparation method thereof

By introducing a flame retardant containing N and P elements into the phenolic resin and a phenolic resin, combined with impregnation and hot pressing forming processes, a high-strength halogen-free flame retardant phenolic paper base laminate was prepared, which solved the current resistance of the current technology The problem of insufficient combustion capacity and environmental protection achieves both excellent flame retardant and mechanical properties.

CN119266026APending Publication Date: 2025-01-07BEIJING FRIEND CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411395258.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When existing phenolic resin paper base laminates improve flame retardant, commonly used halogen-containing flame retardants are restricted by environmental regulations. Adding these agents will cause the mechanical properties of the materials to decline, making it difficult to meet more stringent international environmental regulations and mechanical strength. Require.

Method used

Phenol resin is prepared by introducing N and P elements-containing flame retardants such as alkyl hypophosphites in the phenolic resin, combined with phenol, paraformaldehyde, dicyandiamide and oxalic acid reaction, and high-pressure molding processes are prepared by impregnation and hot-pressing molding processes Strength halogen-free flame-retardant phenolic paper base laminate.

Benefits of technology

The high strength and excellent flame retardant properties of halogen-free flame retardant phenolic paper base laminate are achieved, reaching the vertical combustion level V-0, while maintaining good mechanical properties and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119266026A_ABST
    Figure CN119266026A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength halogen-free flame-retardant phenolic paper-based laminated board and a preparation method thereof, and belongs to the field of insulating laminated board materials. According to the invention, a phenolic resin composition is used as a resin matrix, a paper base material is impregnated by the phenolic resin composition to prepare a prepreg, and then the prepreg is subjected to hot press molding to obtain the high-strength halogen-free flame-retardant phenolic paper-based pressure plate. The phenolic resin composition comprises the following raw materials in parts by weight: 100 parts of phenol, 20-70 parts of paraformaldehyde, 10-80 parts of dicyandiamide, 0.5-7 parts of oxalic acid, 10-50 parts of a flame retardant and 0.1-2 parts of a defoaming agent, and a solvent is added to adjust the solid content to 40-80%. The phenolic paper-based pressing plate prepared by the invention has the advantages of excellent flame retardance (vertical combustion grade V-0) and high bending strength (gt; 180 MPa), and the electrical property is excellent. Meanwhile, halogen is not contained, so that the environment-friendly property is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating laminate materials, in particular to a high-strength halogen-free flame-retardant phenolic paper-based laminate and a preparation method thereof. Background Art

[0002] Phenolic resin paper-based laminates have good mechanical and electrical properties and are mainly used in electrical and electrical, rail transportation, aerospace insulation structural parts or electronic circuit substrates. In the application field of circuit boards, in order to increase the safety of electrical equipment, stricter flame retardant requirements are put forward for phenolic resin paper-based laminates. Compared with other substrate laminates, cellulose paper-based laminates are more difficult to flame retard, and the flame retardancy of its composite materials almost entirely depends on the flame retardancy of the resin. At present, the main method to give phenolic resin paper-based laminates flame retardancy is to add halogen-containing flame retardants to the system. However, with the upgrading of various environmental protection regulations in recent years, the use of halogen-containing flame retardants such as bromine has been increasingly restricted. For example, IEC61249-2-21 has set limits on halogen-free electronic materials. Therefore, the use of elements containing N, P and other elements to improve the flame retardancy of phenolic resin paper-based laminates is a solution that is more in line with current environmental protection requirements. However, the addition of such flame retardants often causes a significant decrease in the mechanical properties of the material. If phosphorus-containing groups are introduced into phenolic, the preparation process will be complicated. In short, in the face of more stringent international environmental regulations, it is urgent to develop halogen-free flame-retardant phenolic resin paper-based laminates with simple process, excellent flame retardant effect and good mechanical strength to meet the needs of industry development. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a high-strength halogen-free flame-retardant phenolic paper-based laminate and a preparation method thereof, and the technical scheme thereof is as follows:

[0004] A high-strength halogen-free flame-retardant phenolic paper-based laminate takes a phenolic resin composition as a resin matrix, prepares a prepreg by impregnating a paper substrate with the phenolic resin composition, stacks and layers the obtained prepreg sheets, and then obtains the high-strength halogen-free flame-retardant phenolic paper-based laminate by hot pressing.

[0005] As a further embodiment of the present invention, the preparation process of the phenolic resin composition comprises the following steps:

[0006] 1) Add phenol, paraformaldehyde, dicyandiamide and oxalic acid into a solvent and heat to the reaction temperature under stirring;

[0007] 2) Heat preservation and stirring reaction;

[0008] 3) After the reaction is completed, cool to room temperature to obtain phenolic resin;

[0009] 4) Adding a flame retardant and a defoamer to the phenolic resin, stirring thoroughly, and then adding a solvent to adjust the solid content to obtain the phenolic resin composition.

[0010] As a further embodiment of the present invention, the ratio of the phenol, paraformaldehyde, dicyandiamide, oxalic acid, solvent, flame retardant and defoamer is as follows:

[0011] 100 parts of phenol, 20-70 parts of paraformaldehyde, 10-80 parts of dicyandiamide, 0.5-7 parts of oxalic acid, 5-50 parts of solvent, 10-50 parts of flame retardant, 0.1-2 parts of defoaming agent;

[0012] The solvent includes one or more of dimethylformamide, dimethylacetamide, ethylene glycol methyl ether, ethylene glycol ethyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, and methyl isobutyl ketone.

[0013] As a further solution of the present invention, in step 1, the reaction temperature is 80-130° C.; in step 2, the reaction time with heat preservation and stirring is 0.5-5 h.

[0014] As a further solution of the present invention, the flame retardant is an alkyl hypophosphite, and the defoamer is one or more of a polysiloxane defoamer, a mineral oil defoamer, and a star polymer defoamer.

[0015] The structural formula of the alkyl hypophosphite is shown in Formula I:

[0016]

[0017] Among them, R1 and R2 are the same or different C1-C6 alkyl groups, M is one of Al, Mg, Ca, Zn, Fe, Na, and K; and m is a positive integer of 1-4.

[0018] As a further solution of the present invention, in step 4, the adjusted solid content is 40%-80%.

[0019] As a further embodiment of the present invention, the paper substrate is one or more of bleached wood pulp paper, kraft paper, and unbleached impregnated insulating paper.

[0020] As a further embodiment of the present invention, a method for preparing a high-strength halogen-free flame-retardant phenolic paper-based laminate comprises the following steps:

[0021] Step 1, immersing the paper substrate into a paint tank filled with a phenolic resin composition for impregnation;

[0022] Step 2: sending the impregnated paper substrate into an oven, keeping warm and drying it, and taking it out from the oven after drying to obtain a prepreg;

[0023] Step 3: Laying the prepreg;

[0024] Step 4: placing the prepreg after layering into a hot press for hot pressing;

[0025] Step 5: After the hot pressing is completed, the plate is cooled and taken out to obtain the high-strength halogen-free flame-retardant phenolic paper-based laminate.

[0026] As a further embodiment of the present invention, in step 1, the immersion time of the immersion process is 1-10 minutes;

[0027] In step 2, the heat preservation and drying temperature is 130-180° C., the drying time is 1-10 minutes, and the glue content of the obtained prepreg is 30-75%.

[0028] As a further solution of the present invention, in step 4, the hot pressing conditions are: the initial temperature of the hot pressing is 110-135°C, the temperature is gradually increased to 140-170°C, and the temperature is maintained for 0.5-4h.

[0029] Compared with the prior art, the beneficial effects of the present invention are:

[0030] The present invention uses phenol, polyformaldehyde, dicyandiamide, and oxalic acid in appropriate proportions to react and prepare a phenolic resin containing the following N-containing structure (structural formula as shown in Formula II), which enables the resin to have good intrinsic flame retardancy and excellent mechanical strength. On this basis, by introducing a P-containing additive flame retardant (alkyl hypophosphite) into the phenolic resin composition, through the synergistic effect of N, P and other elements in the intrinsic & additive flame retardant, the material has a flame retardancy of vertical combustion grade V-0, while maintaining excellent mechanical properties and electrical properties. In addition, the laminate does not contain halogen and has excellent environmental protection.

[0031] BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a photo of the laminate obtained in Example 1.

[0033] Figure 2 This is a photo of the laminate obtained in Example 2.

[0034] Figure 3 This is a photo of the laminate obtained in Example 3.

[0035] Figure 4 This is a photo of the laminate obtained in Example 4.

[0036] Figure 5 This is a photo of the laminate obtained in Example 5.

[0037] Figure 6 This is a photo of the laminate obtained in Example 6. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments. The embodiments described below are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] 1. Preparation of phenolic resin composition

[0041] 38.35g of phenol, 18.34g of paraformaldehyde, 8.55g of dicyandiamide, and 1.3g of oxalic acid were added to 7.67g of dimethylformamide, and the mixture was heated to 90°C and kept for 2h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 5.75g of diethylaluminum hypophosphite and 0.38g of BYK-018 (polysiloxane defoamer) were added to the phenolic resin, and dimethylformamide was added after sufficient stirring to adjust the solid content of the system to 65%, thereby obtaining a phenolic resin composition.

[0042] 2. Preparation of prepreg

[0043] The unbleached impregnated insulating paper was immersed in a paint tank containing a phenolic resin composition, taken out after immersion for 5 minutes, sent into an oven, and dried at 140° C. for 8 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 55%.

[0044] 3. Hot pressing

[0045] The prepreg was layered and then placed in a hot press. The initial temperature was set to 110°C and the initial pressure was 10MPa. The pressure was gradually increased to 40MPa. The temperature was gradually increased to 155°C and the temperature was maintained for 1.5 hours. After the hot press was completed, the laminate was cooled and taken out to obtain a laminate. Figure 1 .

[0046] Example 2

[0047] 1. Preparation of phenolic resin composition

[0048] 38.35g of phenol, 11.51g of paraformaldehyde, 26.8g of dicyandiamide and 1.92g of oxalic acid were added to 5.4g of dimethylacetamide, and the mixture was heated to 110°C and kept for 0.5h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 10g of dimethyl calcium hypophosphite and 0.327g of BYK-018 (polysiloxane defoamer) were added to the phenolic resin, and after sufficient stirring, ethylene glycol ether was added to adjust the solid content of the system to 45% to obtain a phenolic resin composition.

[0049] 2. Preparation of prepreg

[0050] The unbleached impregnated insulating paper was immersed in a paint tank containing a phenolic resin composition, taken out after immersion for 5 minutes, sent into an oven, and dried at 150° C. for 3 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 55%.

[0051] 3. Hot pressing

[0052] The prepreg was layered and then placed in a hot press. The initial temperature was set to 125°C and the initial pressure was 10MPa. The pressure was gradually increased to 40MPa. The temperature was gradually increased to 170°C and the temperature was kept constant for 0.5h. After the hot press was completed, the laminate was cooled and taken out to obtain a laminate. Figure 2 .

[0053] Example 3

[0054] 1. Preparation of phenolic resin composition

[0055] 38.35g of phenol, 23.01g of paraformaldehyde, 17.1g of dicyandiamide, and 0.38g of oxalic acid were added to 5.4g of ethylene glycol methyl ether, and the mixture was heated to 80°C and kept for 2h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 13.4g of diethyl sodium hypophosphite and 0.19g of dimethyl silicone oil were added to the phenolic resin, and after sufficient stirring, ethylene glycol methyl ether was added to adjust the solid content of the system to 45%, to obtain a phenolic resin composition.

[0056] 2. Preparation of prepreg

[0057] The kraft paper was immersed in a paint tank containing a phenolic resin composition, taken out after immersion for 2 minutes, sent into an oven, and dried at 170° C. for 2 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 45%.

[0058] 3. Hot pressing

[0059] The prepreg was layered and then placed in a hot press. The initial temperature was set to 135°C and the initial pressure was 10MPa. The pressure was gradually increased to 40MPa. The temperature was gradually increased to 140°C and the temperature was kept constant for 4 hours. After the hot press was completed, the laminate was cooled and taken out to obtain a laminate. Figure 3 .

[0060] Example 4

[0061] 1. Preparation of phenolic resin composition

[0062] 38.35g of phenol, 18.34g of paraformaldehyde, 8.55g of dicyandiamide, and 1.2g of oxalic acid were added to a mixed solvent of 1g of dimethylformamide and 0.9g of ethylene glycol ethyl ether, and the mixture was heated to 90°C and kept for 1h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 8g of potassium diethyl hypophosphite and 0.38g of dimethyl silicone oil were added to the phenolic resin, and after sufficient stirring, dimethylformamide was added to adjust the solid content of the system to 60%, to obtain a phenolic resin composition.

[0063] 2. Preparation of prepreg

[0064] The bleached wood pulp paper was immersed in a paint tank containing a phenolic resin composition, taken out after being immersed for 7 minutes, sent into an oven, and dried at 150° C. for 6 minutes. After being taken out, a prepreg was obtained, and its glue content was 65%.

[0065] 3. Hot pressing

[0066] The prepreg is laid. Then put into the hot press, set the initial temperature to 120℃, the initial pressure to 10MPa, gradually pressurize to 40MPa, and gradually increase the temperature to 160℃, keep warm and keep pressure for 2h. After the hot press is completed, cool and take out to get the laminate. Figure 4 .

[0067] Example 5

[0068] 1. Preparation of phenolic resin composition

[0069] 38.35g of phenol, 18.34g of paraformaldehyde, 8.55g of dicyandiamide and 1.3g of oxalic acid were added to 7.67g of dimethylformamide, and the mixture was heated to 90°C and kept for 2h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 5.75g of diethylaluminum hypophosphite and 0.38g of BYK-018 (polysiloxane defoamer) were added to the phenolic resin, and after sufficient stirring, ethylene glycol methyl ether was added to adjust the solid content of the system to 55% to obtain a phenolic resin composition.

[0070] 2. Preparation of prepreg

[0071] The kraft paper was immersed in a paint tank containing a phenolic resin composition, taken out after being immersed for 5 minutes, sent into an oven, and dried at 150° C. for 6 minutes. After being taken out, a prepreg was obtained, and its glue content was 55%.

[0072] 3. Hot pressing

[0073] The prepreg is laid and then placed in a hot press. The initial temperature is set to 120°C and the initial pressure is 15MPa. The pressure is gradually increased to 40MPa. At the same time, the temperature is gradually increased to 155°C. The temperature and pressure are kept for 1 hour. After the hot press is completed, it is cooled and taken out to obtain a laminate. Figure 5 .

[0074] Example 6

[0075] 1. Preparation of phenolic resin composition

[0076] 38.35g of phenol, 18.34g of paraformaldehyde, 7.67g of dicyandiamide and 1.3g of oxalic acid were added to 5.4g of dimethylformamide, and the mixture was heated to 90°C and kept for 2h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 11g of dimethyl calcium hypophosphite and 0.25g of BYK-018 (polysiloxane defoamer) were added to the phenolic resin, and dimethylacetamide was added after sufficient stirring to adjust the solid content of the system to 55% to obtain a phenolic resin composition.

[0077] 2. Preparation of prepreg

[0078] The unbleached impregnated insulating paper was immersed in a paint tank containing a phenolic resin composition, taken out after being immersed for 5 minutes, sent into an oven, and dried at 155° C. for 5 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 52%.

[0079] 3. Hot pressing

[0080] The prepreg is laid and then placed in a hot press. The initial temperature is set to 120°C and the initial pressure is 15MPa. The pressure is gradually increased to 40MPa. At the same time, the temperature is gradually increased to 155°C and the temperature is maintained for 2 hours. After the hot press is completed, it is cooled and taken out to obtain a laminate. Figure 6 .

[0081] Comparative Example 1

[0082] 1. Preparation of phenolic resin composition

[0083] 38.35 g of phenol, 14.58 g of polyformaldehyde, and 3.6 g of ammonia water were added to methanol, and the temperature was raised to 100° C. and kept for 1 hour under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 5.75 g of diethyl aluminum hypophosphite and 0.38 g of BYK-018 (polysiloxane defoamer) were added to the phenolic resin, and after sufficient stirring, methanol was added to adjust the solid content of the system to 65%, thereby obtaining a phenolic resin composition.

[0084] 2. Preparation of prepreg

[0085] The unbleached impregnated insulating paper was immersed in a paint tank containing a phenolic resin composition, taken out after immersion for 5 minutes, sent into an oven, and dried at 140° C. for 8 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 55%.

[0086] 3. Hot pressing

[0087] The prepreg is layered and then placed in a hot press. The initial temperature is set to 110°C and the initial pressure is 10MPa. The pressure is gradually increased to 40MPa. The temperature is gradually increased to 155°C and the temperature is maintained for 1.5 hours. After the hot press is completed, it is cooled and taken out to obtain a laminate.

[0088] Comparative Example 2

[0089] 1. Preparation of phenolic resin composition

[0090] 38.35g of phenol, 18.34g of paraformaldehyde, 8.55g of dicyandiamide and 1.3g of oxalic acid were added to 7.67g of dimethylformamide, and the mixture was heated to 90°C and kept for 2h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 0.38g of BYK-018 (polysiloxane defoamer) was added to the phenolic resin, and dimethylformamide was added after sufficient stirring to adjust the solid content of the system to 65%, thereby obtaining a phenolic resin composition.

[0091] 2. Preparation of prepreg

[0092] The unbleached impregnated insulating paper was immersed in a paint tank containing a phenolic resin composition, taken out after immersion for 5 minutes, sent into an oven, and dried at 140° C. for 8 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 55%.

[0093] 3. Hot pressing

[0094] The prepreg is layered and then placed in a hot press. The initial temperature is set to 110°C and the initial pressure is 10MPa. The pressure is gradually increased to 40MPa. The temperature is gradually increased to 155°C and the temperature is maintained for 1.5 hours. After the hot press is completed, it is cooled and taken out to obtain a laminate.

[0095] Comparative Example 3

[0096] 1. Preparation of phenolic resin composition

[0097] 38.35g of phenol, 18.34g of paraformaldehyde, 8.55g of dicyandiamide, and 1.3g of oxalic acid were added to 7.67g of dimethylformamide, and the mixture was heated to 90°C and kept for 2h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 5.75g of ammonium polyphosphate and 0.38g of BYK-018 (polysiloxane defoamer) were added to the phenolic resin, and dimethylformamide was added after sufficient stirring to adjust the solid content of the system to 65%, thereby obtaining a phenolic resin composition.

[0098] 2. Preparation of prepreg

[0099] The unbleached impregnated insulating paper was immersed in a paint tank containing a phenolic resin composition, taken out after immersion for 5 minutes, sent into an oven, and dried at 140° C. for 8 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 55%.

[0100] 3. Hot pressing

[0101] The prepreg is layered and then placed in a hot press. The initial temperature is set to 110°C and the initial pressure is 10MPa. The pressure is gradually increased to 40MPa. The temperature is gradually increased to 155°C and the temperature is maintained for 1.5 hours. After the hot press is completed, it is cooled and taken out to obtain a laminate.

[0102] Comparative Example 4

[0103] 1. Preparation of phenolic resin composition

[0104] 38.35g of phenol, 18.34g of paraformaldehyde, 8.55g of dicyandiamide, and 1.3g of oxalic acid were added to 7.67g of dimethylformamide, and the mixture was heated to 90°C and kept for 2h under stirring. Then the mixture was cooled to room temperature to obtain a phenolic resin. 19.2g of ammonium polyphosphate and 0.38g of BYK-018 (polysiloxane defoamer) were added to the phenolic resin, and dimethylformamide was added after sufficient stirring to adjust the solid content of the system to 65%, thereby obtaining a phenolic resin composition.

[0105] 2. Preparation of prepreg

[0106] The unbleached impregnated insulating paper was immersed in a paint tank containing a phenolic resin composition, taken out after immersion for 5 minutes, sent into an oven, and dried at 140° C. for 8 minutes. After being taken out, a prepreg was obtained, and the glue content of the prepreg was 55%.

[0107] 3. Hot pressing

[0108] The prepreg is layered and then placed in a hot press. The initial temperature is set to 110°C and the initial pressure is 10MPa. The pressure is gradually increased to 40MPa. The temperature is gradually increased to 155°C and the temperature is maintained for 1.5 hours. After the hot press is completed, it is cooled and taken out to obtain a laminate.

[0109] Table 1 Performance of the laminated board in the embodiment

[0110]

[0111] Table 2 Performance of the laminate in the comparative example

[0112]

[0113] As can be seen from the data in Tables 1 and 2, the vertical combustion grade of the laminated boards prepared by the present invention can reach V-0, and the bending strength can reach above 180 MPa, so it has both excellent combustion performance and mechanical strength. In addition, since it does not contain halogen, it has excellent environmental protection.

[0114] If ordinary phenolic resin (whose structural formula is shown in Formula III) is compounded with alkyl hypophosphite (Comparative Example 1), or the phenolic resin of the present invention is used but no additional flame retardant is added (Comparative Example 2), the corresponding laminated board cannot reach the flame retardancy of V-0 level, and the mechanical properties of the former are significantly lower than those of the laminated board prepared by the present invention. If the phenolic resin of the structure described in the present invention is used and ammonium polyphosphate is added as a flame retardant, the corresponding laminated board cannot reach the flame retardancy of V-0 level under the same proportion (Comparative Example 3 vs Example 1); if a large amount of ammonium polyphosphate is added (Comparative Example 4), the flame retardancy can reach V-0, but the bending strength of the corresponding laminated board is greatly reduced.

[0115]

[0116] Test example

[0117] According to the process of Example 1, the amount of diethylaluminum hypophosphite was adjusted, and the results are shown in Table 3:

[0118] Table 3 Relationship between the amount of diethyl aluminum hypophosphite and flame retardancy

[0119] The ratio of diethyl aluminum hypophosphite to phenol 0 5% 10% ≥15% Vertical burning level (thickness 1mm) V-2 V-2 V-1 V-0 Vertical burning grade (thickness 3mm) V-2 V-1 V-0 V-0

[0120] In addition, it should be understood that those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A high-strength halogen-free flame-retardant phenolic paper-based laminate, characterized in that: The phenolic resin composition is used as the resin matrix, and a prepreg is prepared by impregnating a paper substrate with the phenolic resin composition. The obtained prepreg sheets are stacked and laid, and then the high-strength halogen-free flame-retardant phenolic paper-based laminate is obtained by hot pressing.

2. The high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 1, characterized in that: The preparation process of the phenolic resin composition comprises the following steps: 1) Add phenol, paraformaldehyde, dicyandiamide and oxalic acid into a solvent and heat to the reaction temperature under stirring; 2) Heat preservation and stirring reaction; 3) After the reaction is completed, cool to room temperature to obtain phenolic resin; 4) Adding a flame retardant and a defoamer to the phenolic resin, stirring thoroughly, and then adding a solvent to adjust the solid content to obtain the phenolic resin composition.

3. The high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 2, characterized in that: The proportions of the phenol, paraformaldehyde, dicyandiamide, oxalic acid, solvent, flame retardant and defoamer are as follows: 100 parts of phenol, 20-70 parts of paraformaldehyde, 10-80 parts of dicyandiamide, 0.5-7 parts of oxalic acid, 5-50 parts of solvent, 10-50 parts of flame retardant, 0.1-2 parts of defoaming agent; The solvent includes one or more of dimethylformamide, dimethylacetamide, ethylene glycol methyl ether, ethylene glycol ethyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, and methyl isobutyl ketone.

4. The high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 2, characterized in that: In step 1, the reaction temperature is 80-130° C.; in step 2, the reaction time with heat preservation and stirring is 0.5-5 h.

5. The high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 2, characterized in that: The flame retardant is alkyl hypophosphite, and the defoamer is one or more of a polysiloxane defoamer, a mineral oil defoamer, and a star polymer defoamer.

6. The high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 2, characterized in that: In step 4, the adjusted solid content is 40%-80%.

7. The high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 1, characterized in that: The paper substrate is one or more of bleached wood pulp paper, kraft paper, and unbleached impregnated insulating paper.

8. A method for preparing a high-strength halogen-free flame-retardant phenolic paper-based laminate according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, immersing the paper substrate into a paint tank filled with a phenolic resin composition for impregnation; Step 2: sending the impregnated paper substrate into an oven, keeping warm and drying it, and taking it out from the oven after drying to obtain a prepreg; Step 3: Laying the prepreg; Step 4: placing the prepreg after layering into a hot press for hot pressing; Step 5: After the hot pressing is completed, the product is cooled and taken out to obtain the high-strength halogen-free flame-retardant phenolic paper-based laminate.

9. The method for preparing a high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 8, characterized in that: In step 1, the dipping time of the dipping process is 1-10 minutes; In step 2, the heat preservation and drying temperature is 130-180° C., the drying time is 1-10 minutes, and the glue content of the obtained prepreg is 30-75%.

10. The method for preparing a high-strength halogen-free flame-retardant phenolic paper-based laminate according to claim 8, characterized in that: In step 4, the hot pressing conditions are as follows: the initial temperature of the hot pressing is 110-135° C., the temperature is gradually increased to 140-170° C., and the temperature is maintained for 0.5-4 hours.

Citation Information

Patent Citations

  • Preparation method of halogen-free flame-retardant phenolic aldehyde laminated paper board

    CN104401073A

  • Flame-retarded resin and preparation method thereof

    CN104497249A

  • Phenolic resin composition for flame-retardant wet curtain as well as preparation method and application of phenolic resin composition

    CN104532582A